PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBANTUAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP PEMAHAMAN KONSEP IPAS SISWA KELAS V - Azizi Zamzam; Patricia H.M Lubis, Henni Riyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the Contextual Teaching and Learning (CTL) model assisted by flipbook media on students’ conceptual understanding in the subject of Natural and Social Sciences (IPAS) for fifth-grade students at SD Negeri 07 Palembang. The research employed a quasi-experimental method with a non-equivalent control group design, involving class VA as the experimental group and class VB as the control group. Data were collected through pre-test and post-test using multiple-choice instruments that had been validated for validity and reliability. The experimental class was taught using the CTL model with flipbook media, while the control class received conventional learning through lectures and simple discussions. The results showed that the CTL model assisted by flipbook media had a significant effect on students’ conceptual understanding. The independent sample t-test indicated a significance value of 0.030 (< 0.05), meaning that there was a significant difference in the post-test scores between the two groups. The average post-test score of the experimental class was 94.55, while the control class only reached 60.73. Furthermore, the analysis of conceptual understanding indicators revealed that the experimental class experienced higher and more evenly distributed improvements, with some indicators achieving perfect scores. Therefore, it can be concluded that the CTL learning model assisted by flipbook media is effective in improving students’ conceptual understanding in IPAS, especially on the topic of electrical energy.